2022-RA-686-ESGO Paradigm shift in surgical approach in the management of advanced ovarian cancer in the university hospitals of LEICESTER. (20th October 2022) - Barakat, Anas; Ismail, Aemn; Chattopadhyay, Supratik
Abstract : Introduction/Background: Surgery for advanced ovarian cancer (AOC) has evolved over the past decade to ingeminate the need to offer maximum effort surgery (MES) with the aim of complete cytoreduction (R0 resection), to improve survival. The objective of this study is to analyse the implementation of a paradigm shift in the surgical management of women with AOC at the University Hospitals of Leicester NHS Trust (UHL) in 2015, until 2020, compared to 2011–2014. Methodology: Retrospective cohort study of women with AOC who underwent cytoreductive surgery (CRS). The two groups were: 153 women from January 2011 to December 2014 (group 1), 136 women from January 2015 to January 2020 (group 2). Results: In group 1, the 1 year, 3 years and 5 years overall survival rates (OS) were, 90.4%, 33.7% and 19.3%, compared to 90.2%, 55.4% and 29.7%, respectively, in group 2 (p=0.012). Significantly more women had CRS in group 2: 45 – Primary debulking surgery (PDS) and 57 – interval debulking surgery (IDS) vs. 17 – PDS & 67 – IDS in group 1 (P<0.001). Surgical complexity score (modified Aletti score) was higher in group 2 compared to group 1 (p≤0.001). No significant difference was noted in the postoperative complications, in group 2, in women who underwent PDS vs. IDS, yet PDS was associated with higher OS. Conclusion: The transition from standard surgery to maximal effort surgery in AOC patients (a paradigm shift in surgical approach) had a positive impact on OS and PFS rates in our institution. Our data highlights the importance of a dedicated team to implement this change in cancer centres treating AOC. In women who had maximum effort cytoreductive surgery from 2015 onwards, PDS was associated with higher survival rates and comparable post-operative complications than IDS although the surgical complexity was higher in the PDS group.